Gender differences in the reactivity of normoglycemic and diabetic rat aorta and the effects of quercetin and 17β-estradiol / Aloysius Umelo Iguegbe - Aloysius, Umelo Iguegbe (2012)
Background & objectives: Diabetes is a stronger risk factor in the development of cardiovascular diseases in the female than the male gender. Diabetes-induced reactive oxygen species (ROS) alters the function of endogenous vasoconstrictors for which the antioxidant, quercetin, has been shown to restore in diabetic male rats, which has not been proven in the female. The female hormone, estradiol (a potent antioxidant), combined with quercetin may offer greater protection against diabetes/ROS-induced vascular reactivity. Therefore, the influence of gender on the response of normoglycemic/diabetic aorta to vasoconstrictors in the presence/absence of quercetin/estradiol, including mechanisms underlying any differences in tissue responses was examined. Materials & methods: Isometric tension to cumulative concentrations of phenylephrine or angiotensin II were recorded in (age-and-sex-matched) thoracic aorta isolated from normoglycemic/streptozotocin-treated Wistar Kyoto rats. The role of ROS, 17β-estradiol, antioxidant enzymes, nitric oxide (NO) and prostaglandins (PG) in modulating the differences were explored. Results & Discussion: Endothelium-intact normoglycemic male tissues contracted more to PE or Ang II than the female or the diabetic male. The normoglycemic (proestrus or diestrus) /diabetic female tissues contracted equally to PE. Ang II caused lesser contraction of normoglycemic (proestrus) /diabetic compared to normoglycemic female tissues in diestrus state. Endothelial-denudation or blockade of L-NAME/methylene blue (MB) pre-treatment reversed these differences, suggesting e-NOS-sGC-cGMP pathway regulated the differences. Endothelial-denudation, L-NAME/MB and acetylcholine produced lesser effect on the normoglycemic male and diabetic male/female tissues iii Gender differences in the reactivity of normoglycemic and diabetic rat aorta and the effects of quercetin and 17β-estradiol compared to the normoglycemic female, which exhibited higher tissue vasorelaxants (NO/PGI2). Therefore, the aorta of healthy female rat exists in a higher eNOS-sGC-cGMP (basal vasorelaxant) state. This feature was reversed by diabetes, supporting the hypothesis that the female vasculature succumbs more to diabetes-induced alterations than the male. Contractile PG levels were higher in normoglycemic male/diabetic female tissues. Diabetes promoted relaxant PGI2 synthesis in male/female tissues. This result is consistent with observed gender difference in tissue contraction (normoglycemic male >female and diabetic female>male). Higher diabetic female synthesis of contractile PGs consistently supports the greater negative impact of diabetes in the female. Enhanced diabetic-synthesis of vasodilators (PGI2/EDNO) in male (/female) tissues perhaps represents a pathologic feature of short-term diabetes to counter increased diabetic state-stimulated contraction. These findings have implications for further understanding of the gender-related differences in the mechanism of diabetes-induced vascular disease. The order of tissue oxidative stress and quercetin-induced reduction are diabetic (male >female)>normoglycemic (male >female) tissues, suggesting that quercetin effect is partially mediated by its action against oxidative stress. 17β-estradiol and/or quercetin-induced relaxation was greater in phenylephrine compared to angiotensin II-contracted diabetic male/female tissues, suggesting that quercetin/estradiol therapy appears more clinically relevant in managing phenylephrine than angiotensin II-mediated vasoreactivity during diabetes. L-NAME/MB reversed quercetin effect in normoglycemic male/female tissues (with/without endothelium) and male/female diabetic tissues (with but not without endothelium). L-NAME+indomethacin reduced quercetin effect in endothelium-intact iv Gender differences in the reactivity of normoglycemic and diabetic rat aorta and the effects of quercetin and 17β-estradiol normoglycemic male and diabetic male/female tissues. Hence, quercetin action is partly mediated by endothelium-sensitive (eNO-sGC-cGMP/cyclooxygenase) and-insensitive (NO/cGMP) mechanisms, the latter of which appears inactive in male/female diabetic tissues. These findings have implication for the potential therapeutic usefulness of quercetin in the management of diabetes vascular disease.